Finite Element Analysis of Plastic Behavior in RC Beam Supports with Composite Steel Deck Slabs under Cyclic Loading - Brihaspati, Brihaspati; Saputra, Ashar; Setiawan, Angga Fajar; Sulistyo, Djoko (Institute of Research and Community Outreach - Petra Christian University, 2026)
The performance of beam supports is essential for seismic resilience, particularly under the Strong Column–Weak Beam (SCWB) principle. To improve construction efficiency, steel deck-based composite slabs are increasingly adopted as alternatives to conventional slabs. However, their impact on the plastic behavior of beam supports remains underexplored. This study evaluates the influence of steel deck slabs using finite element analysis in ABAQUS. Two beam-column joint models—conventional and modified—were subjected to cyclic loading according to FEMA 461. The models incorporated stiffness recovery, combined hardening for steel, and a cohesive zone model (CZM) for the concrete–steel deck interface. Results indicate that the steel deck model shows a wider hysteresis loop and 2.425% higher energy dissipation, but experiences earlier reinforcement yielding and greater stiffness degradation. Although ductility increases, plastic hinges form at nearly the same cycle. Overall, the steel deck system improves energy absorption and ductility but reduces elastic stiffness and accelerates inelastic behavior.